Developing family-centred care in a neonatal intensive care unit: An action research study. (February 2019) - Skene, Caryl; Gerrish, Kate; Price, Fiona; Pilling, Elizabeth; Bayliss, Pauline; Gillespie, Siobhan
Abstract: Aim: To develop, implement and evaluate family-centred interventions to promote parental involvement in caregiving in a Neonatal Intensive Care Unit. Methodology: A participatory action research approach was used to implement two changes in practice a) improved skin-to-skin contact b) unlimited parental presence at the cot-side. The changes were underpinned by a family-centred philosophy of care and education. Data were collected from staff using a questionnaire, focus groups and interviews, and from parents using focus groups and interviews. Qualitative data were analysed using Framework and quantitative data analysed using descriptive and t -test statistics. Setting: A Neonatal Intensive Care Unit in England. Findings: Changes in practice were successfully implemented. Nurses reported positively on improvements in Family Centred Care; most notably information-sharing with parents, providing family support, enabling parental participation in care and improved competence supporting parents in care-giving. These changes were reflected in parental feedback. Conclusion: Understanding the context of the neonatal unit can support cultural change when change is actively facilitated and owned by the staff concerned. Acknowledging parents as the main caregiver can be challenging for nurses and they require support and education to enable them to manage the changes necessary to provide Family-Centred Care.